Addressing the Needs of Vulnerable Youth : Buenos Aires Second Secondary Education Project - Cesilini, Sandra (World Bank, Washington, DC, 2012)
The Province of Buenos Aires government's strategy for secondary school education aims to improve equity, quality, and effectiveness. To support these objectives, the provincial Ministry of Education proposed a new program, "Jornada Completa" or "Full Day Schedule" to be introduced in 200 pilot schools. The program will be supported by the World Bank through the Buenos Aires Second Secondary Education project. The pilot program seeks to ensure equity by paying special attention to the quality of education for children "at risk." Jornada Completa will increase the number of classroom hours from 800 per year to 1,200 per year and introduce a new pedagogic and curricular model. Extending the school day is also intended to lessen students' exposure to street violence. The program will support measures designed to make school management more effective and more autonomous. School selection criteria will target those urban lower secondary schools in which most of the student enrollment comes from households that are considered socially and economically disadvantaged and among the poorest. On the basis of the pilot results, the government intends to gradually extend the Jornada Completa to all secondary schools in high poverty districts or areas.